Integrated Test Solutions for a System Design Environment. Issue 4 (1994) - Kornegay, Kevin T.; Brodersen, Robert W.
Abstract : While the performance, density, and complexity of application-specific systems increase at a rapid pace, equivalent advances are not being made in making them more easily testable, diagnosable, and maintainable. Even though testability bus standards, like JTAG Boundary Scan, have been developed to help eliminate these costs, there exists a need for efficient hardware and software tools to support them. Hence, a testability design and hardware support environment for application-specific systems is described which provides a designer with a set of hardware modules and circuitry, that support these standards and software tools for automatic incorporation of testability hardware, as well as automatic test vector and test program generation.